2020
DOI: 10.33448/rsd-v9i11.9728
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and rheological evaluation of blends based on ora-pro-nóbis (Pereskia aculeata Miller) and wheat flour

Abstract: This work aimed to evaluate the nutritional and rheological quality of ora-pro-nobis flour (OPNF) and its influence on the replacement of wheat flour (WF), through the analysis of physicochemical parameters, determination of phenolic compounds, antioxidant activity and rheological analyzes of wheat flour and mixtures with 10 to 30% OPNF. Flour blends with 10%, 20% and 30% of OPNF in substitution of WF in flour base were evaluated. The OPNF showed higher values of lipids (2.87%), proteins (18.29%), fibers (44.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Source: Authors. Trentin et al (2020) also showed increased nutritional quality and antioxidant activity of regular wheat flour partially substituted by ora-pro-nobis flour. In a dose dependent manner, the substitution of 0, 10, 20 and 30% regular flour for ora-pronobis flour increased total phenolic content from 0.56 to 7.6, 14.51 and 21.5 gallic acid equivalents per gram, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Source: Authors. Trentin et al (2020) also showed increased nutritional quality and antioxidant activity of regular wheat flour partially substituted by ora-pro-nobis flour. In a dose dependent manner, the substitution of 0, 10, 20 and 30% regular flour for ora-pronobis flour increased total phenolic content from 0.56 to 7.6, 14.51 and 21.5 gallic acid equivalents per gram, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…The plant is easily grown, as it is rustic, perennial and propagates easily. Its planting method is the use of cuttings, for providing greater efficiency, shortening its production cycle (Trentin et al, 2020). Rooting strength, in addition to the quality and quantity of cuttings (with the latter being healthy and vigorous matrices), varies according to species type, environmental conditions, growing method, besides the internal condition of the plant itself (Madeira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…PANCs include Pereskia aculeata Miller, popularly known in Brazil as ora-pro-nobis. (Brasil, 2010;Trentin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%